Epidemic roller coaster: maize stunt disease in Nicaragua - Hruska, A.J.; Gladstone, S.; Obando Solis, S.R. (New York (EUA), 1996)
Resumen (Es)
Graf; Cuadr., 25 ref.
Keywords: ZEA MAYS; SPIROPLASMA; DALBULUS MAIDIS; ENFERMEDADES TRANSMITIDAS VECTORES